Prevalence of Mucopolysaccharidosis I in A Paediatric and Young Adult Population, Diagnosed with Carpal Tunnel Syndrome - Ly-Pen, Domingo; Andreu, José-Luis; Blas, Gema de; Sánchez-Olaso, Alberto; Jiménez San Emeterio, Jesús (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Mucopolysaccharidosis type I (MPS-I: Hurler/Scheie´s disease) is a rare disease with a wide spectrum of severity. This results in underdiagnosis and delayed diagnosis. Prognosis greatly depends upon early diagnosis. The availability of reliable diagnostic tests and the existence of enzyme replacement therapy and/or hematopoietic stem cell transplantation, make an early diagnosis of these patients extremely important. Carpal tunnel syndrome (CTS) is among one of the most common findings in MPS I, whilst CTS is very uncommon in infancy and young adulthood. Objective: To ascertain the prevalence of MPS-I among children and young adults (≤ 30 years) diagnosed with CTS in our population. To get an early diagnosis of MPS-I patients. Material and Methods: This is a cross-sectional prospective study of a cohort of patients with an electromyogram-confirmed diagnosis of CTS. Our total population is over 600,000 people of an urban area of Madrid. We searched for children and young adults with suggestive symptoms of CTS. χ2 for categorical variables and Student “t” analysis or Anova test for quantitative variables were used. Results: 12 patients were included, 10 females, range 8-28 years, mean 23, median 23.5. Two patients had a low α-L-Iduronidase activity. Nonetheless, the results of confirmatory test of enzymatic activity of α-L-Iduronidase in lymphocytes were negative in both cases. Conclusions: We did not find any MPS-I in our series of CTS in children and young adults. Larger series will be needed to ascertain if this approach is valid for early diagnosis of MPS-I in the paediatric population.